Prognostic consequence of hyperglycemia points in oral glucose intolerance test for the course and outcomes of pregnancy in women with gestational diabetes mellitus - I. V. Bunak; M. I. Sviridova; N. M. Startseva; Yu. A. Hamoeva (Сахарный диабет, 2025)
BACKGROUND: The level of glycemia at different points of the glucose tolerance test measure different phases of insulin secretion, accordingly the groups of pregnant women with GDM diagnosed at different points of the test have differences.AIM: to evaluate the impact of oral glucose tolerance test results for frequency of insulin treatment, incidence of preeclampsia and pregnancy outcomes in women with GDM.MATERIALS AND METHODS: Retrospective analysis of 200 maternal medical cards and hospital cards of birth in women with GDM for the period 2021–2022. The patients were divided into two groups according the results of OGTT: 1st group — 102 pregnant women with fasting hyperglycemia, 2nd group — 98 pregnant women with hyperglycemia in 1 and 2 hours after glucose intake. Differences in age, body weight, BMI, weight gain during pregnancy, therapy of GDM were studied, and the incidence of preeclampsia and pregnancy outcomes were assessed in both groups.RESULTS: women of the 1st group had significantly higher weight and initial BMI. Pregnant women of both groups with a BMI over 25 kg/m2 more often required insulin treatment. The incidence of preeclampsia, newborn weight and the incidence of macrosomia were higher in 1st group.CONCLUSION: Fasting hyperglycemia in OGTT is associated with overweight and obesity, and these women are more likely to require insulin therapy. Women with GDM diagnosed by fasting hyperglycemia are at grate risk of developing preeclampsia and macrosomia.